FISH FARMERS MOTIVATION TOWORD FISH FARMING BUSINESS OF BAUNG (Mystus nemurus) IN THE POOL OF SUNGAI PAKU VILLAGE SUB-DISTRICT OF KAMPAR KIRI KAMPAR DISTRICT RIAU PROVINCE - Fadillah, Umi; Nugroho, Firman; ', Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on July 2015 in Sungai Paku Village Sub-district of Kampar Kiri Kampar District Riau Province. This research aimed to gain the level of fish farmers motivation as well as the relationship between the characteritics of fish farmers and fish farmers motivation of Baung (Mystus nemurus) in the pool. The method used in this research was survey method with the number of 35 respondents of fish farmers of Baung (Mystus nemurus).Based on the research result, it was found that the level of fish farmers motivation of Baung (Mystus nemurus) was moderate (4209) that was fish farmers motivation still depending on the conditian and certain cabability as thr side jobs. Whereas, the relationship between characteritics the fish farmers and fish farmers motivation of Baung (Mystus nemurus) in the pool had the relation to motivation with education and motivation with family members were moderate and very significant. However, the relation motivation with age, income, capital, business experience and the number of working times were very weak and insignificant.Keyword : fish farmer of Baung (Mystus nemurus), motivation fish farmers